A pore way to die: the role of mitochondria in reperfusion injury and cardioprotection. (26th July 2010) - Halestrap, Andrew P.
Abstract : In addition to their normal physiological role in ATP production and metabolism, mitochondria exhibit a dark side mediated by the opening of a non-specific pore in the inner mitochondrial membrane. This mitochondrial permeability transition pore (MPTP) causes the mitochondria to breakdown rather than synthesize ATP and, if unrestrained, leads to necrotic cell death. The MPTP is opened in response to Ca 2+ overload, especially when accompanied by oxidative stress, elevated phosphate concentration and adenine nucleotide depletion. These conditions are experienced by the heart and brain subjected to reperfusion after a period of ischaemia as may occur during treatment of a myocardial infarction or stroke and during heart surgery. In the present article, I review the properties, regulation and molecular composition of the MPTP. The evidence for the roles of CyP-D (cyclophilin D), the adenine nucleotide translocase and the phosphate carrier are summarized and other potential interactions with outer mitochondrial membrane proteins are discussed. I then review the evidence that MPTP opening mediates cardiac reperfusion injury and that MPTP inhibition is cardioprotective. Inhibition may involve direct pharmacological targeting of the MPTP, such as with cyclosporin A that binds to CyP-D, or indirect inhibition of MPTP opening such as with preconditioning protocols. These invoke complex signalling pathways to reduce oxidative stress and Ca 2+ load. MPTP inhibition also protects against congestive heart failure in hypertensive animal models. Thus the MPTP is a very promising pharmacological target for clinical practice, especially once more specific drugs are developed.